Disability after prolonged mechanical ventilation in the intensive care unit: tracking the fate of our patients - Ball, Lorenzo; Pelosi, Paolo (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
The occurrence of a critical illness initiates a complex chain of pathophysiologic, psychological and social mechanisms, contributing to a relevant burden of care and affecting long-term outcome. Clinical routine offers a partial perspective on this issue to the intensive care unit (ICU) caregivers: often seen as the last relevant event in patients’ history, ICU discharge is actually the beginning of a long path towards recovery, requiring efforts from the patients, their families and healthcare systems.